ENHANCING PERFORMANCE IN SMES: A CONCEPTUAL FRAMEWORK FOR AI ADOPTION THROUGH DIGITAL READINESS AND EMPLOYEE DIGITAL SKILLS - Mustafa, Hasfah Nurhanum; Ab Ghani, Nur Izzati; Adam, Asrul (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
In today’s rapidly changing digital era, the adoption of Artificial Intelligence (AI) is transforming business operations by enhancing efficiency, innovation, and productivity. Small and Medium-sized Enterprises (SMEs), which play a vital role in driving economic growth, often struggle to leverage AI for competitive advantage. Despite the significant potential of AI to enhance SME performance, adoption rates remain relatively low due to technological and organizational barriers. This study applies the Technology-Organization-Environment (TOE) framework to investigate the factors influencing AI adoption in SMEs which impact on performance. This study, focuses on proposed conceptual model which combines technological factors (digital readiness) and organizational factors (employee digital skills) as key determinants of AI adoption. It seeks to bridge the gap in existing research by providing a structured approach to assess in-depth understanding into TOE constructs such as digital infrastructure readiness and employee digital skills. As a research proposal, this study will employ Exploratory Factor Analysis (EFA) and Reliability Analysis Cronbach’s Alpha to validate the conceptual model, followed by Structural Equation Modelling (SEM) to examine relationships among key constructs. This finding will provide valuable insights for SMEs top management, government. policymakers and technology players by offering effective guidelines to enhance AI adoption and drive sustainable growth in the SMEs.